Evaluasi Pendidikan Budaya dan Sosial Masyarakat di Gampong Meunasah Asan Lhoksukon Kabupaten Aceh Utara Provinsi Aceh - Saputra, Andika (Medan Resource Center, 2023)
Each educational institution employs planning and evaluation in its execution; thus, the education delivered must align with the societal and cultural ethos, as education and social culture share the closest nexus among communities. General education is imperative to nurture all facets of religious, cultural, and social education. Meunasah Asan village, situated in Lhoksukon district, plays a crucial role in imparting diverse teachings to its varied populace, tailored to their needs. Through field observations, cultural and social evaluations underscore the village's cohesive methodology across all domains. Collaborative efforts in communal activities, be it communal cleanup or religious gatherings, exemplify the village's unified approach. Consequently, cultural and social education must be upheld for posterity, ensuring the continuity of traditions and values for future generations and the preservation of religious sanctity.